Current-mode multiphase sinusoidal oscillator using CDTA-based allpass sections - Tangsrirat, Worapong; Tanjaroen, Wason; Pukkalanun, Tattaya (My University, 2009)
In this work, a current tunable current-mode multiphase sinusoidal oscillator (MSO) employing current differencing transconductance amplifier (CDTA)-based first-order allpass sections is presented. The proposed MSO circuit, which uses only two CDTAs and one virtually grounded capacitor for each phase, can generate arbitrary 2 n-phase current-output signals (n = 2, 3, 4, ...) equally spaced in phase, all at high output impedance terminals. The oscillation condition and the oscillation frequency can be controlled electronically and independently by adjusting the bias current of the CDTA. The oscillator has low-sensitivity performance. Simulation results are also given to verify the functionality of the proposed oscillator. © 2008 Elsevier GmbH. All rights reserved.
Keywords: Allpass filter; Current differencing transconductance amplifier (CDTA); Current-mode circuits; Multiphase sinusoidal oscillator (MSO)